2008
DOI: 10.1007/s10640-008-9198-8
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Discontinuous Preferences into the Analysis of Discrete Choice Experiments

Abstract: Data from a discrete choice experiment on improvements of rural landscape attributes are used to investigate the implications of discontinuous preferences on willingness to pay estimates. Using a multinomial error component logit model, we explore differences in scale and unexplained variance between respondents with discontinuous and continuous preferences and condition taste intensities on whether or not each attribute was considered by the respondent during the evaluation of alternatives.Results suggest tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
139
2
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 190 publications
(152 citation statements)
references
References 50 publications
7
139
2
4
Order By: Relevance
“…2 Differences in scale between both the test and the retest might be caused by effects such as learning, fatigue, complexity and consistency as various studies have shown (e.g. Breffle and Rowe 2002;Holmes and Boyle 2005;Campbell et al 2008;Carlsson et al 2012). In the present case a learning effect might occur as respondents face the same choice sets a second time.…”
Section: Parametric Analysis and Willingness-to-pay Estimatesmentioning
confidence: 77%
See 2 more Smart Citations
“…2 Differences in scale between both the test and the retest might be caused by effects such as learning, fatigue, complexity and consistency as various studies have shown (e.g. Breffle and Rowe 2002;Holmes and Boyle 2005;Campbell et al 2008;Carlsson et al 2012). In the present case a learning effect might occur as respondents face the same choice sets a second time.…”
Section: Parametric Analysis and Willingness-to-pay Estimatesmentioning
confidence: 77%
“…We present two pooled models, one without and one with scale parameter. The scale parameter is explicitly included (in contrast to using a grid-search procedure) and estimated by full information maximum likelihood (Campbell et al 2008;Olsen 2009). For the subset of choices monitored at the first point in time (the test) the scale parameter is arbitrarily normalised to one while the scale parameter for the subset of choices monitored at the second point in time (the retest) is allowed to vary.…”
Section: Parametric Analysis and Willingness-to-pay Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…of rural landscape attributes, Campbell et al (2008) find that discontinuous preferences help explain the magnitude and robustness of willingness to pay estimates.…”
Section: Ecological Economicsmentioning
confidence: 87%
“…However, in focus groups and in pilot studies, we learned that there was a risk that some respondents would not pay proper attention to the cost-for-the-household attribute. There is a growing literature indicating that this is the case for many stated preference surveys (see, e.g., Gilbride Campbell, 2008;Hensher, 2008;Scarpa et al, 2009). Therefore, we chose to use a latent class model following Scarpa et al (2009).…”
Section: Econometric Modelmentioning
confidence: 96%